2023
DOI: 10.1371/journal.pone.0289702
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of bee honey on the basis of melissopalynology as well as chemical analysis

Zahra Shakoori,
Ahmadreza Mehrabian,
Dariush Minai
et al.

Abstract: Melissopalynological and chemical analysis of honey provide us useful and valuable information about the botanical and geographical origin of honey. The data in question is very important for authentication as well as for testing the quality of honey, so this is considered the main method in honey regulation here, we have used chemical analysis and melissopalynology to evaluate different honey samples from two main Iranian hubs of honey. Sampling was carried out on two important poles in Iran’s honey productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
0
4
0
1
Order By: Relevance
“…The ecological results of this study showed that the abundance of Rosaceae and Fabaceae families, which play an effective role in the antioxidant activity of honey, rise with increasing altitude. Therefore, it seems that the increase in antioxidant activity due to the rise in altitude up to 3000 m above the surface of open water 48 is largely influenced by the abundance of these two families. For example, the Rosaceae family grows in high areas 72 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ecological results of this study showed that the abundance of Rosaceae and Fabaceae families, which play an effective role in the antioxidant activity of honey, rise with increasing altitude. Therefore, it seems that the increase in antioxidant activity due to the rise in altitude up to 3000 m above the surface of open water 48 is largely influenced by the abundance of these two families. For example, the Rosaceae family grows in high areas 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Alborz and Zagros are the habitats of many 2597 native vascular plant species in Iran 51 , 52 . The diverse plant communities of Zagros and Alborz and the highlands of Azerbaijan have turned them into hubs of honey production in Iran 48 . Therefore, these areas were chosen to collect honey samples (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have highlighted the significant role of pollen analysis in verifying the authenticity of honey. Sniderman et al pioneered the application of pollen analysis to authenticate Australian honeys’ geographical origin, while Shakoori et al emphasized the importance of chemical and pollen analysis in evaluating honey quality and origin, revealing polyfloral compositions across 42 plant families. The origin of Hungarian honey was determined using melissopalynology, physicochemical analysis, and NIR spectroscopy, surpassing NIR’s success rate with over 90% accuracy .…”
Section: Visualization and Discussionmentioning
confidence: 99%
“…Mengacu pada metode melisopalinologi dan analisis kimia yang dijelaskan dalam penelitian dari Shakoori, et al (2023), bahwa dengan mempertimbangkan faktor geografis dan ekologis yang mempengaruhi keanekaragaman tanaman sumber polen. Penelitian ini menunjukkan bahwa kondisi ekologis yang berbeda, seperti variasi iklim dan topografi yang kompleks, dapat menciptakan lingkungan lebah yang berharga dan menghasilkan madu yang sangat beragam.…”
Section: Zea Mays Famili Chenopodiaceaeunclassified